Improving Students' Ability to Understand Redox Reactions Using Jigsaw Techniques - Sunardi, Endi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2018)
This study is aimed at finding descriptions about : a) to what extent Jigsaw Technique can improve students’ ability in comprehending of the Redoks reaction at grade XI ATP of SMK N 4 Muaro Jambi, and b) factors that influence the changes of students’ ability in comprehension of Redoks reaction at grade XI ATP of SMKN 4 Muaro Jambi. The design of the research is Classroom Action Research. The research is conducted in three Cycles. At each cycle, it is administered in four phases, namely: Plan, Action, Observation, and Reflection. The participants of the research are the students at grade XI ATP of SMKN Muaro Jambi in the 2017-2018 academic years. The instruments of the research consist of; tests, and observation checklists. The data were analyzed using quantitative and qualitative techniques. The findings of the research are: a) the use of Jigsaw Technique could improve the students’ ability in comprehension of the Redoks reactions at grade XI ATP of SMKN 4 Muaro Jambi, b) the factors that influence the changes of the students’ ability in comprehension of Redoks reaction: redoks reaction material, teaching technique, and classroom management. Based on the findings the researcher suggsets English teachers who have the same problem to use jigsaw technique to solve their problems in teaching to comprehend the redoks reaction and the future researchers are expected to do the research on the other skills.